1984
DOI: 10.1128/mcb.4.11.2306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of the glucoamylase gene of Aspergillus awamori.

Abstract: The filamentous ascomycete Aspergillus awamori secretes large amounts of glucoamylase upon growth in medium containing starch, glucose, or a variety of hexose sugars and sugar polymers. We examined the mechanism of this carbon source-dependent regulation of glucoamylase accumulation and found a several hundredfold increase in glucoamylase mRNA in cells grown on an inducing substrate, starch, relative to cells grown on a noninducing substrate, xylose. We postulate that induction of glucoamylase synthesis is reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(63 citation statements)
references
References 65 publications
2
60
1
Order By: Relevance
“…X I 0 0 has not been cloned and we are unable to make specific mutant forms. However, the corresponding gene from A. awamori [24], which is identical to the gene isolated from A. niger [15], is available for molecular engineering. We are therefore able to compare the NMR spectra of glucoamylases from both of these with mutant forms.…”
mentioning
confidence: 99%
“…X I 0 0 has not been cloned and we are unable to make specific mutant forms. However, the corresponding gene from A. awamori [24], which is identical to the gene isolated from A. niger [15], is available for molecular engineering. We are therefore able to compare the NMR spectra of glucoamylases from both of these with mutant forms.…”
mentioning
confidence: 99%
“…N-terminal amino acid sequence of GA I was ATLDSWLSNEATVARTA. This sequence showed complete homology with glucoamylase from A. awamori (Nunberg et al, 1984), A. niger (Boel et al, 1984) and A. shirousamii (Shibuya et al, 1990). However, only 11 residues were homologous with that of glucoamylase from A. oryzae (Hata et al, 1991).…”
Section: Resultsmentioning
confidence: 93%
“…Nunberg reported that raw starch adsorption domain of glucoamylase is located near the C-terminal region, and that the TS domain serves as hinge portion between the N-terminal and the C-terminal regions (Nunberg et al, 1984). α-amylases of Aspergillus sp., including Amyl I, do not have TS domain and they are unable to digest raw starch.…”
Section: Discussionmentioning
confidence: 99%
“…M. pusillus and Rhizopus belong to the same class, the Zygomycetes, but the MPR gene lacks an intron in contrast to the glucoamylase gene of the latter. The pattern of codon usage in the MPR gene is similar to those in several filamentous fungi such as Aspergillus (25,28), Trichoderma (27) and Neurospora (23), but different from that in S. cerevisiae (17) especially with respect to the codons for Arg, Cys, Gln, Leu and Pro. Correlation of the gene structures with phylogenic groups will be a future problem in the taxonomy of filamentous fungi and yeasts.…”
Section: Nucleic Acids Researchmentioning
confidence: 82%
“…although the genes of the extracellular glucoamylase from Aspergillus and Rhizopus fungi (25,26) and the extracellular cellulase from Trichoderma reesei (27) have been found to possess intron sequences. M. pusillus and Rhizopus belong to the same class, the Zygomycetes, but the MPR gene lacks an intron in contrast to the glucoamylase gene of the latter.…”
Section: Nucleic Acids Researchmentioning
confidence: 99%